Effect of linear and quadratic coupling on dynamical parameters of an optomechanical oscillator: Linear and quadratic coupling in optomechanical oscillator - Le, Tri Dat; Pham, Vinh N. T.; Le, Van Tan; Vy, Nguyen Duy (Communications in Physics, 2025)
Dynamics of icrocantilevers are of important interest in micro-mechanical systems for enhancing the functionality and applicable range of the cantilevers in vibration transducing and highly sensitive measurement. In this study, using the semi-classical Hamiltonian formalism, we study in detail the modification of the mechanical frequency and damping rate taking into account both the linear and quadratic coupling between the mechanical oscillator and the laser field in an opto-mechanical system. It has been seen that, the linear coupling greatly enhances the modification of the effective mechanical frequency and the effective damping rate while the quadratic coupling reduces these quantities. For a MHz-frequency oscillator, the damping rate could be 10^5 times increased and the frequency is several times modified. These results help clarifying the origin of the modification of the susceptibility function for cooling of the mechanical mode.